2016
DOI: 10.1007/s40264-016-0469-y
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-Induced Thrombocytopenia: A Narrative Review

Abstract: Thrombocytopenia has been reported as an adverse reaction of numerous drugs. Vancomycin is often overlooked as a culprit but has been associated with several cases of thrombocytopenia that were not well described in the literature. A literature search was conducted to find reports of thrombocytopenia induced by vancomycin. Biomedical databases including 'PubMed', 'Scopus', and 'Web of Science' were searched using terms 'vancomycin', 'platelet', 'pancytopenia', 'thrombocytopenia', and 'bleeding'. English langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 56 publications
1
33
0
1
Order By: Relevance
“…28 A recent review shows an association between the highest trough level of vancomycin and thrombocytopenia. 29 However, the platelet counts might be a surrogate of organ dysfunction or disease severity. 30 Aubron et al 31 indicated that peak and trough concentration was lower in patients with severe organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…28 A recent review shows an association between the highest trough level of vancomycin and thrombocytopenia. 29 However, the platelet counts might be a surrogate of organ dysfunction or disease severity. 30 Aubron et al 31 indicated that peak and trough concentration was lower in patients with severe organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet transfusion is not indicated owing to continued immune destruction of the platelets in the presence of the offending agent [3]. However, transfusion can be considered in cases of severe bleeding and platelet counts less than 20 Â 10 3 /mm 3 [2] and can be effective when performed after discontinuation of the causative agent [15].…”
Section: Discussionmentioning
confidence: 99%
“…There is no gold standard regarding testing for VIT currently; however, the standard antibiotic-induced immune thrombocytopenia (AIT) clinical and laboratory criteria are generally recommended for suspected cases. Management has typically consisted of discontinuation of the causative medication, with transfusion being the next most commonly used treatment in the case of severe bleeding and some studies estimating transfusion rates as high as 2 of 3 patients [2]. Other treatments including corticosteroids, immunoglobulins, and plasma exchange have been used; however, none of these were clinically superior in a large retrospective series of 30 patients with VIT [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations